REMOVAL OF BASIC DYE BY MAGNETICALLY MODIFIED ACTIVATED CARBON - Tanyildizi, M. Saban; Demirci, Yavuz; Altundogan, H. Soner (Parlar Scientific Publications (P S P), 2018)
In this study, adsorption of basic dye (Basic yellow X-5GL) was investigated by magnetically modified activated carbon, which is easily separated from aqueous medium. The effect of adsorption variables was determined by using Design of Experiment (DOE). Also, the characterization adsorption process was investigated. Central Composite Design (CCD), which also describes interaction effect of independent variables, was used for obtaining the model equation for the adsorption process. Three important variables (initial concentration of the dye, initial pH of the solution and amount of adsorbent) were studied using CCD for the process. We designed our experiments to obtain a quadratic model of 20 trials consisting factorial, stars and center points. ANOVA results show that good correlation between the predicted and experimental values. The statistical evaluations show that the results of DOE are properly fitted, considering the determination coefficient (R-2=0.99) for dye removal. The highest adsorption capacity (181.4 mg/g) was obtained under the conditions of 0.66 g/l of the sorbent dosage, 9.34 of the initial pH and 234 mg/l of the dye concentration.
Keywords: Paramagnetic activated carbon; Basic Yellow X-5GL; Design of Experiment